2018
DOI: 10.1007/s00592-018-1253-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and mortality events in type 2 diabetes cardiovascular outcomes trials: a systematic review with trend analysis

Abstract: Aims To investigate cardiovascular disease and mortality trends in control arm participants of diabetes cardiovascular outcome trials (CVOTs). Methods We electronically searched CVOTs published before October 2017. Data on all-cause mortality, cardiovascular mortality and events, and baseline characteristics were collected, along with study calendar years. Trends were estimated using negative binomial regressions and reported as rate ratio (RR) per 5-year intervals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…The decreasing trends in cardiovascular and non-cardiovascular hospitalisations and mortality in subjects with T2D are not dissimilar to previous findings [ 32 , 33 ]. Gregg et al.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The decreasing trends in cardiovascular and non-cardiovascular hospitalisations and mortality in subjects with T2D are not dissimilar to previous findings [ 32 , 33 ]. Gregg et al.…”
Section: Discussionsupporting
confidence: 49%
“…The decreasing trends in cardiovascular and non-cardiovascular hospitalisations and mortality in subjects with T2D are not dissimilar to previous findings [32,33]. Gregg et al reported that between 1971Gregg et al reported that between and 1986Gregg et al reported that between and 1988 to 2000, the all-cause mortality rate reduced by 18.2 deaths per 1000 person-years in men with diabetes [32].…”
Section: Discussionmentioning
confidence: 46%
“…The primary aim of the present study was to compare the risk of different CVD event phenotypes across ethnic groups. The low incidence of CVD events, which occurred at rates lower than those observed in type 2 diabetes mellitus cardiovascular outcome trials and primarily related to the absence of prevalent CVD at baseline 21 , hampered the possibility to reliably quantify the excess risk of all CVD phenotypes in each ethnic group including the risk of aortic aneurism, myocardial infarction and other CVD-related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong interest in demonstrating both the CV safety and the CV benefit of all antidiabetic agents, especially for macrovascular complications. CV outcomes trials have evaluated the CV safety and efficacy profile of some of these agents [ 10 ]. As a result, the recently published ADA/European Association for the Study of Diabetes (EASD) consensus statement recommends the use of sodium-glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in patients with T2DM with established CVD or high CV risk [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%